2009
DOI: 10.1007/s12024-009-9116-6
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arterial medial smooth muscle thickness in sudden infant death syndrome: an analysis of subsets of 73 cases

Abstract: Previous studies addressing pulmonary artery morphology have compared cases of sudden infant death syndrome (SIDS) to controls but none have compared demographic profiles, exposure to potentially hypoxic risk factors and other pathologic variables in SIDS cases grouped according to pulmonary artery medial smooth muscle thickness. Aims: To compare the relative medial thickness (RMT) in alveolar wall arteries (AW) in SIDS cases with that in age-matched controls and 2. Compare demographic, clinical, and pathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Sympathetic activation/catecholamine release in response to hypoxia/hypercapnia is mediated by carotid body glomus cells acutely (143) and by peripheral chemoreceptor organs [e.g., adrenal medulla and oxygen sensing pulmonary neuroendocrine cells (PNEC)] (144). Lungs from infants dying of SIDS have demonstrated hyperplasia of PNEC with reduced myelination of its vagal afferents impairing oxygen sensing (145) as well as increased airway (146) and thick pulmonary arteries in males (147). …”
Section: Introductionmentioning
confidence: 99%
“…Sympathetic activation/catecholamine release in response to hypoxia/hypercapnia is mediated by carotid body glomus cells acutely (143) and by peripheral chemoreceptor organs [e.g., adrenal medulla and oxygen sensing pulmonary neuroendocrine cells (PNEC)] (144). Lungs from infants dying of SIDS have demonstrated hyperplasia of PNEC with reduced myelination of its vagal afferents impairing oxygen sensing (145) as well as increased airway (146) and thick pulmonary arteries in males (147). …”
Section: Introductionmentioning
confidence: 99%
“…Muscularization of normally nonmuscularized peripheral vessels is the result of the release of endothelial vasoconstrictors, growth factors, matrix proteins and adhesion molecules as a cellular response to hypoxia. 10,13 Although our cases fell under the spectrum of Sudden Unexpected Death in Infancy (SUDI), there shared some unusual findings: both died in hospital after a short history of unexplained respiratory deterioration: Case 1 had been increasingly breathlessness with grunting for 2 days, and then presenting with shortness of breath and tachycardia and subcostal recession before arrest; Case 2 suddenly struggled to breathe and died shortly after admission. Hypoxia-induced smooth muscle proliferation in pulmonary arteries requires several days, 10 so at first sight it seems unlikely that the short-lived respiratory symptoms in our cases had any influence in the muscularization of the intraacinar arteries.…”
Section: Discussionmentioning
confidence: 81%
“…Williams et al 9 study on 15 consecutive SIDS and controls showed an extension of muscle in arteries not usually muscularized, as well as an increase in the percentage of medial wall thickness in some SIDS participants, therefore corroborating Naeye's results. 8 Krous et al, 10 retrospectively, compared the relative medial thickness in alveolar wall arteries, pre-acinar and intraacinar arteries as well as the demographic, clinical and pathological features in 19 SIDS cases with 19 agematched controls. All cases and controls in their study 10 were >28 days of age, while our cases were 12 and 28 days old.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations